Mathletics [ how gamblers, managers, and sports enthusiasts use mathematics in baseball, basketball, and football - Winston, Wayne L. (Princeton : Princeton University Press, 2009)
How does professional baseball evaluate hitters? Is a singles hitter like Wade Boggs more valuable than a power hitter like David Ortiz? This title shows readers how to use simple mathematics to
Description based on print version record
Includes bibliographical references and index
Keywords: Sports -- Mathematics